68Ga‐PSMA‐11 PET‐CT study in prostate cancer patients with biochemical recurrence and non‐contributive 18F‐Choline PET‐CT: Impact on therapeutic decision‐making and biomarker changes. Issue 5 (14th December 2018) - Barbaud, Matthieu; Frindel, Mathieu; Ferrer, Ludovic; Le Thiec, Maelle; Rusu, Daniela; Rauscher, Aurore; Maucherat, Bruno; Baumgartner, Pierre; Fleury, Vincent; Colombié, Mathilde; Thierry‐Morel, Agnes; Kraeber‐Bodéré, Françoise; et al.
Abstract : Background: In this retrospective study, we investigated the impact of 68 Ga‐PSMA‐11 PET‐CT (PSMA PET‐CT) upon the treatment plan and therapeutic response obtained for Prostate Cancer (PCa) patients presenting an occult biochemical recurrence. Methods: Forty‐two patients with previously negative or doubtful 18F‐Choline (FCH) were enrolled. PET images were recorded 1 h after injection of tracer. Only a few months after treatment ended, a PSA assay was requested to evaluate the therapeutic efficacy of the treatment based on PSMA results. Results: PSMA—positive lesions were detected in 34/42 (80.9%) patients. Detection rates were 85.7% and 89.3% for serum PSA levels lower than 2 ng/mL, and >2 ng/mL, respectively. One hundred seventy‐three lesions were detected: 132/173 in lymph nodes (76.3%), 22/173 as metastatic sites (bone or lung) (12.7%), and 19/173 in the prostate bed (10.9%). As a result of the PSMA PET‐CT, therapeutic management changed in 31/42 patients (73.8%). With a follow‐up of 4.9 ± 2.27 months, 32/42 (76.2%) PSA assays after treatment guided by PSMA PET‐CT were collected. For 37.5% (12/32) of patients, the serum PSA level was lower than 0.2 ng/mL and a PSA decrease of over 50% in 8 (25.0%) other patients were obtained. Conclusion: Performing a PSMA PET‐CT when FCH PET‐CT was doubtful or negative allows the recurrence localization in more 80% of patients and this had a major clinical impact, as it resulted in treatment change in more than 70% of patients as well as a significant decrease in PSA levels in more than 60% of them.